Psychiatric disorders as risk factors for the development of type 2 diabetes mellitus: an umbrella review protocol. Issue 5 (30th May 2019) - Lindekilde, Nanna; Nefs, Giesje; Henriksen, Jan Erik; Lasgaard, Mathias; Schram, Miranda; Rubin, Katrine; Rutters, Femke; Kivimaki, Mika; Pouwer, Frans
Abstract : Introduction: Numerous longitudinal studies, systematic reviews and meta-analyses have examined psychiatric disorders as risk factors for the development of type 2 diabetes mellitus. A more comprehensive overview of the area is warranted to summarise current evidence and discuss strengths and weaknesses to guide future research. Aim: The aim of this umbrella review is to determine whether and to what extent different psychiatric disorders are associated with the development of type 2 diabetes mellitus. Furthermore, the umbrella review also assesses the evidence on potential mediating mechanisms. Methods and analysis: The present umbrella review will consist of a comprehensive systematic search of published systematic reviews and meta-analyses of observational longitudinal studies investigating whether a psychiatric disorder is associated with the risk of developing type 2 diabetes. PubMed, Embase, PsychINFO and the Cochrane Database of Systematic Reviews will be searched, and the results will be screened for inclusion by two independent reviewers. Furthermore, the reference lists of included publications will be manually searched. Two independent reviewers will extract data and assess the methodological quality in the included systematic reviews and meta-analyses. Evidence on potential mediating mechanisms included in the systematic reviews and meta-analyses will also be reviewed. The implications of the overview will be discussed in light of the quality of the included studies, and suggestions for clinical practice and future research will be made. Ethics and dissemination: Ethical approval is not required for this umbrella review. Our review will be submitted for publication in a peer-reviewed international journal using open access option if available. The results will also be disseminated at international conferences. PROSPERO registration number: CRD42018096362